Potenciación de las prácticas agrícolas ancestrales en el ámbito turístico en la parroquia Vilcabamba, cantón Loja - Bermeo Cano, Kelsi Paola (2019)
Tourism in one of the most important economic activities with the country account; the different types of tourism that exist today, this industry generates jobs, infrastructure works, gastronomic and hotel developments among others, as well as in its importance, the care of each country to develop tourism in a sustainable manner. Each country, town or community has history, traditions and cultures that make the times different, the cultural heritage is a main axis and that allows us to know, value and preserve the ancestral practices that even the participants, therefore the present study has as purpose Contribute to local tourism development through the "Enhancement of Ancestral Agricultural Practices in the Tourist Area in Vilcabamba Parish, Canton Loja", within the stated objectives. A general objective was set for the development of the research: "To boost the ancestral agricultural practices of the parish of Vilcabamba, Loja canton," as well as specific objectives such as: "To identify the ancestral agricultural practices of the parish of Vilcabamba adopted through of generations "," Propose a tourism product to enhance ancestral agricultural practices "and" Establish strategies that allow enhancing the defined tourism product ". The methodology of Carla Ricaurte was used through the tourist diagnosis sheets for communities, after which the inventory and ranking sheets of tourist attractions of the MINTUR 2017, summary records, as well as the techniques of direct observation and interviews were carried out. to the authorities and people involved in agriculture that allowed the development of a SWOT (Strengths, Weaknesses, Opportunities and Threats) matrix, from which strategies were identified for the design of a tourism product, its brand, creation of an agro-tourism route consisting of two itineraries that will allow to know about the ancestral agricultural practices, their diffusion and promotion so that this tourist product can be developed. Regarding the results obtained from the research, it is concluded that the Vilcabamba parish has a good tourist infrastructure, food services, accessibility and adequate transportation, tourist attractions with access in good conditions, the majority of the adult population lives from agriculture where they have an infinity of ancestral practices and techniques that must be strengthened and rescued to preserve them from generation to generation, and so the tourist can know, value, and practice ancestral agriculture. In view of this situation, it is proposed to develop a tourism product, where an agrotourism route was designed with the purpose of encouraging 11 tourist activity; an internal and external analysis of the farms with which the agrotourism route is going to be carried out was made and it was evidenced that the parish of Vilcabamba has a great tourist potential capable of attracting visitors to the associated farms, being the agrotourism proposal a fundamental guide in the tourist field. Regarding the results obtained from the research, it is concluded that the Vilcabamba parish has a good tourist infrastructure, food services, accessibility and adequate transportation, tourist attractions with access in good conditions, the majority of the adult population lives from agriculture where they have an infinity of ancestral practices and techniques that must be strengthened and rescued to preserve them from generation to generation, and so the tourist can know, value, and practice ancestral agriculture. In view of this situation, it is proposed to develop a tourism product, where an agrotourism route was designed with the purpose of encouraging tourist activity; an internal and external analysis of the farms with which the agrotourism route is going to be carried out was made and it was evidenced that the parish of Vilcabamba has a great tourist potential capable of attracting visitors to the associated farms, being the agrotourism proposal a fundamental guide in the tourist field.